The Need to Establish and Implement Knowledge Management in the Organization and its Role in Gaining Competitive Advantage - Amozgar, Abdul Khaliq (Journal of Social Sciences - Kabul University, 2023)
The purpose of this study, which has been done by review method, is to investigate the necessity and importance of establishing knowledge management in organizations and also its role in gaining a competitive advantage. In order to achieve the above goal, according to the existing literature and records in the field of study, after analyzing the concept of knowledge, knowledge management and its process, the importance of knowledge management as a competitive advantage has been introduced. The findings show that countries that have surpassed others in creating knowledge are higher in term of competitive advantage. Today, organizations are using brains more than their hands, and the need to apply knowledge is increasing. Knowledge management has reduced operating costs, accelerated new product development, improved customer service and improved individual and organizational performance. Effective knowledge management within the organization is one of the ways to create value and competitive advantage in today's organizations.